The two southernmost species of the Andean genus Acrographinotus Holmgren (Arachnida, Opiliones, Gonyleptidae) described from Bolivia and Argentina - Acosta, Luis E. (Zootaxa, 2024)
Two new species of the genus Acrographinotus (Opiliones, Laniatores, Gonyleptidae) are described from protected areas placed on sub-Andean ranges: Acrographinotus tariquiae sp. nov. from Tariquía National Reserve, southern Bolivia, and A. calilegua sp. nov. from Calilegua National Park, northwestern Argentina. They represent the southernmost representatives, and in the case of A. calilegua sp. nov., the lowest altitudinal record of this wide-ranged Andean genus. Acrographinotus tariquiae sp. nov. is compared with its most similar congeners, A. erectispina (type species) and A. niawpaq, from which it differs by the armature of trochanter IV, femur IV and ventral anal plate of the male. Differences between A. calilegua sp. nov. and A. tariquiae sp. nov., especially considering small-sized and β-type males of the latter, are detailed. The genus diagnosis is updated. A key to identify males of the nine confirmed nominal Acrographinotus species is provided for the first time.